Namibia : Technical Assistance Report-Assessing and Managing Fiscal Risks from State-Entities and Public-Private Partnerships. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance report discusses measures proposed to assess and manage fiscal risks from state-owned entities and public-private partnerships in Namibia. Fiscal risks from public entities (PEs) materialize when funding requirements are higher than expected or revenues shortfalls occur. The government's strategy for managing PE related fiscal risks should be informed by the likelihood of PE experiencing difficulties and, in such an event, the magnitude of the potential impact on the government. A two-step methodology was proposed for assessing the likelihood of fiscal risks materializing from PE. The authorities are also considering legislative amendments to strengthen the institutional arrangements for supervising PE.